Traditional Medicine Using Betel Leaf for The Batubara Community - Lister Berutu; Khairul Zikri; Iqbal Pratama; Wily Simbolon; Noel Putra Hutauruk; Rheysa Tara Nabila (Indonesian Journal of Medical Anthropology, 2023)
Betel leaf is a plant that grows a lot in Indonesia and can be easily found anywhere. The efficacy of betel leaf as a healing drug from various scientific research results concludes that betel has very nutritious ingredients and millions of benefits for health. The tradition of betel nut can strengthen teeth because ancient people already knew the efficacy of green betel leaf which can treat several diseases, this study explains how the benefits of betel leaf for medicinal ingredients. This research was conducted in the Batubara area, the technique of collection. The results of this study indicate that the coal community, treating illnesses such as fever still believes in the traditional way by using betel leaf as medicine.